(3GdcTa GdefJXQ deG jQGg GdeMJVQs - (3HQgGf GdOjf YHO Gddg EHQGgje Hf MSf GdcQOi GdchQGfi GdTgQRhQi GdSgQGfi Ke GdeOfj,J (B1101 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO abO SCdJ CjgG GdCN hGdLhGH GdELeGdi Cf gPG GdJaUjd dG CUd dg ai TF ef cJH GdCMGOjK s
(3BNQgG (B:s
(3adYd GdSjhWi CQGO GdCUd dg UMjMkG aEf GdMOjK GdePchQ ai SfOg hGeG NUhUgeG HNUhU GdUhQJjf adGOdjd Ydjg fbdkG hEf bGdg cTakG adjS cdjkG Je JShjOg hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B35 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B21s
Keywords: (3GdeLGejYs